Paradise of the animals - Almario, Virgilio S.; Joanne De Leon (Quezon City, Philippines : Adarna House Inc., 2004)
More than being a story of how animal life began, this is a book about the value of peace and tolerance.
Keywords: CHILDREN'S LITERATURE -- PHILIPPINES